(-3)-(2)=

Simple and best practice solution for (-3)-(2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-3)-(2)= equation:


Simplifying
(-3) + -1(2) = 0
-3 + -1(2) = 0

Multiply -1 * 2
-3 + -2 = 0

Combine like terms: -3 + -2 = -5
-5 = 0

Solving
-5 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 5p+3=4p+6 | | 20p-2p+4p=20p-6p | | -17x-20=14x+70 | | -4x-11x=-75 | | 2.5x+3=15-1.5x | | 2x+1=4x-15 | | 2x-7=x+6 | | 17-5x=9+3x | | 5x+9=2x+30 | | 2x^2-x+6=0 | | 4x^2-44x+96= | | 7x-1=4x-3 | | 4x+0.2=6.6 | | 5x+4-4x=12-29 | | n^2-n+4=0 | | 5x-11-4x=-5 | | p=4n-50 | | 6k^2+22k-8=0 | | (x+2)(x+5)=-2 | | 4w+12w-10=16w-10 | | (6+4)*2-7+9+18+(5+1*3)+5=688 | | 3(0.6+2n)-3.2=7.6 | | x(x-5)=x^2+3x+5 | | 4x+13x=102 | | x^4-9= | | (6+4)*2-7+9+18+(5+1*3)+5=x | | 2x^2=-9x | | 90x^2+1=6x | | 2.5d=0.4f+50 | | -72x^4-8x^3= | | 3(k+5)=-19 | | 15x^2-26x+8=0 |

Equations solver categories